Pengembangan Media Permainan Ular Tangga Raksasa Pada Mata Pelajaran Pendidikan Pancasila Materi Kerja Sama Di Lingkunganku Untuk Siswa Kelas IV SDN 36 Cakranegara - Ida Ayu Putu Kareninda; Khairun Nisa; Muhammad Sobri (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The learning media used in Pancasila Education at SD Negeri 36 Cakranegara is still limited to images available in student textbooks. These images serve only as visual aids and have not been designed to actively engage students in the learning process. In addition, limited facilities, such as LCD projectors, printers, and internet access, have hindered the optimal use of more diverse learning media. This study aimed to develop a giant snakes and ladders game as a learning medium for the topic Cooperation in My Environment in Pancasila Education for fourth-grade elementary school students, as well as to determine its validity and practicality. This research employed the Research and Development (R&D) method using the ADDIE development model. Data were collected through interviews, observations, questionnaires, and documentation. The data were analyzed using qualitative and quantitative techniques. The result of this study was a giant snakes and ladders game designed as a learning medium for fourth-grade students in Pancasila Education. Validation results showed that the media was categorized as highly valid, with a score of 98% from the media expert and 90% from the material expert. The practicality test based on teacher responses obtained a score of 92% in the small-group trial and 96% in the large-group trial, both categorized as highly practical. Meanwhile, student responses showed practicality scores of 93.1% in the small-group trial and 93.2% in the large-group trial, which were also categorized as highly practical. Therefore, the giant snakes and ladders game is considered valid and practical for use in teaching the topic Cooperation in My Environment in Pancasila Education for fourth-grade elementary school students.